ANALISIS ENTRANCE SURFACE EXPOSURE (ESE) DAN KUALITAS RADIOGRAF PHANTOM SEBAGAI PARAMETER KENDALI MUTU PADA PESAWAT MAMOGRAFI - Erna Mariani; Eko Hidayanto; Evi Setiawati (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2013)
The Entrance Surface Exposure (ESE) and quality of radiograph phantom as part of a Quality Control (QC) were analyzed on mammography machine Hologic M-Series. This research aims to detemine ESE values on mammography machine and determining number of fibers, speck groups and masses on radiograf phantom as part of a Quality Control (QC).The ESE was measured by Multi Purpose Detector (MPD) over the range of kV from 20–27 kV kV for current time 90 mAs, 95 mAs, 100 mAs, and phantom radiograph was tested by CIRS model 015 phantom was exposed at 23 kV for current time 90 mAs, 95 mAs, 100 mAs. The ESE values by direct measurement ranged from 3,22 mGy to 10,86 mGy and The ESE values by calculation of backscatter factor ranged from 3,59 mGy to 11,73 mGy and phantom radiograph testing qualitatively the number of fibers, speck groups, and mass in over the range of tolerances are 4 for fibers, 3 for speck groups, and 3 for the masses. This results shown that the mammography machine is still good condition and proper to be used for clinical examination moreover the result of phantom radiograph can be read properly and can diagnose symptoms of abnormalities in breast tissue properly.Keywords: Entrance Surface Exposure (ESE), phantom radiograph, quality control, mammography machine, Multi Purpose Detector (MPD).